Soil Fertility, Plant Nutrition and Nutrient Management - Lin Tang (Plants)
Soil fertility refers to the ability of soil to sustain agricultural plant growth; fertile soil provides a habitat with essential nutrients and favorable chemical, physical and biological characteristics to sustain plant growth [...]